2024
DOI: 10.1093/nar/gkae238
|View full text |Cite
|
Sign up to set email alerts
|

DEGRONOPEDIA: a web server for proteome-wide inspection of degrons

Natalia A Szulc,
Filip Stefaniak,
Małgorzata Piechota
et al.

Abstract: E3 ubiquitin ligases recognize substrates through their short linear motifs termed degrons. While degron-signaling has been a subject of extensive study, resources for its systematic screening are limited. To bridge this gap, we developed DEGRONOPEDIA, a web server that searches for degrons and maps them to nearby residues that can undergo ubiquitination and disordered regions, which may act as protein unfolding seeds. Along with an evolutionary assessment of degron conservation, the server also reports on pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…However, it is highly unlikely that the HA tag influenced the outcome of the experiment, since growth kinetics and peak titers of the rLCMV-Z-HA were not significantly affected. Bioinformatic analysis revealed that HA-tagged both Z-WT and Z-G2A mutant proteins have five putative degrons [63].The functional degron region, which includes parts of the tripartite model and the tertiary structure necessary for E3 ligase engagement, is predicted to be located within 40 amino acids of the degron motif, whereas the HA tag was positioned more than 50 amino acids away from lysine 38 (K38) of the degron motif, supporting the exclusion of HA as an interfering factor. Moreover, experimental evidence supports that the HA tag does not interfere with C-terminal degrons in other proteins across different systems of eukaryotes [64][65][66][67], and we have shown that LCMV Z protein with a Cterminal HA tag is fully functional in cell-based assays virus [68].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is highly unlikely that the HA tag influenced the outcome of the experiment, since growth kinetics and peak titers of the rLCMV-Z-HA were not significantly affected. Bioinformatic analysis revealed that HA-tagged both Z-WT and Z-G2A mutant proteins have five putative degrons [63].The functional degron region, which includes parts of the tripartite model and the tertiary structure necessary for E3 ligase engagement, is predicted to be located within 40 amino acids of the degron motif, whereas the HA tag was positioned more than 50 amino acids away from lysine 38 (K38) of the degron motif, supporting the exclusion of HA as an interfering factor. Moreover, experimental evidence supports that the HA tag does not interfere with C-terminal degrons in other proteins across different systems of eukaryotes [64][65][66][67], and we have shown that LCMV Z protein with a Cterminal HA tag is fully functional in cell-based assays virus [68].…”
Section: Discussionmentioning
confidence: 99%